DIRECTION OF MAQASHID SHARIAH AS A POLITICAL PHILOSOPHY OF DEVELOPMENT AND MULTICULTURALISM IN INDONESIA - Hermansyah Hermansyah (Muamalat: Jurnal Kajian Hukum Ekonomi Syariah, 2019)
This research is motivated by the thought that most of the development in Muslim countries adopt western development strategy that is not the same characteristics of the ideological and economic situation. The mistake often made ??is what Muslim countries face very difficult economic problems it faces. From the analysis, and then concluded that: First, the failure of development theories in the wake of the Western conception is caused due to the approach used partially. This approach implies the logical consequences that are often neglected, namely: (a) the emphasis on growth ignores the equitable distribution; (b) does not reflect a policy priority; (c) there is no strategy that touches economic problems directly, (d) policies that are run out of balance, so often leads to inequality and injustice. Secondly, one of the approaches used in assessing the performance of the construction of the Islamic perspective using maqashid analysis is an approach that uses concept development and a holistic approach in dealing with and touch all the existing problems and is one of the alternative approaches as a form of revision of the economistic approach to development. Third, using the live view system in formulating a political policy of economic development in Indonesia will open new perspectives in the list to the involvement of maqashid development priorities and multiculturalism. The implication is that the conception of economic development may no longer shut away from the public space in which there are a variety of needs analysis and involves a multicultural society.